Circulating plasma microRNA-126, microRNA-145, and microRNA-155 and their association with atherosclerotic plaque characteristics - Knoka, Evija (J Clin Transl Res, 2020)
AIMS: Circulating microRNAs (miRNAs) have been identified as biomarkers for several diseases. Dysregulation of miRNA-126, microRNA-145, and microRNA-155 has been shown to be associated with atherosclerotic lesion formation. The aim of this study was to evaluate the association between atherosclerosis-related miRNAs and unfavorable atherosclerotic plaque characteristics. METHODS AND RESULTS: Forty patients with stable coronary artery disease admitted for elective percutaneous coronary intervention (PCI) were enrolled in a prospective study. After PCI, intravascular ultrasound (IVUS), and iMAP-IVUS analysis were performed to assess the proportion of fibrotic, necrotic, lipidic, and calcific tissue within atherosclerotic plaques. Total RNA was isolated from plasma to evaluate the expression of circulating miRNA-126, miRNA-145, and miRNA-155. Plasma lipid and glucose metabolism-related variables were measured to determine any association with plaque characteristics or miRNA expression. Expression of miRNA-126 was negatively correlated with plaque fibrotic tissue (r=−0.28; P=0.044), while positively correlated with plaque necrotic tissue (r=0.31; P=0.029) and necrolipidic tissue (r=0.31; P=0.031). MiRNA-145 was positively correlated with plaque lipidic (r=0.32; P=0.023) and necrolipidic tissue (r=0.31; P=0.029). Patient age was associated with plaque fibrotic tissue (r=-0.41; P=0.005), necrotic tissue (r=0.33; P=0.022), and lipid content (r=0.33; P=0.022). High-density lipoprotein cholesterol was positively correlated with plaque necrotic (r=0.28; P=0.042) and calcific (r=0.28; P=0.044) tissue volume. Calcific tissue volume was positively correlated with C-peptide (r=0.34; P=0.033). After multivariate logistic regression analysis, both miRNA-126 and miRNA-145 expressions were associated with increased necrolipidic tissue content (β=0.34; P=0.050; and β=0.35; P=0.037, respectively). CONCLUSIONS: Expressions of miRNA-126 and miRNA-145 were associated with increased plaque necrolipidic tissue content. RELEVANCE FOR PATIENTS: Although further research is needed to support the study data, miRNA-126 and miRNA-145 may serve as potential plaque vulnerability biomarkers in the future.